2006
DOI: 10.1080/15412550500493360
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Bronchi of Patients with COPD Show Decreased Histamine Responsiveness Compared to Smokers with Normal Lung Function

Abstract: This study compared airway responsiveness in vitro, as measured in isolated bronchi, with responsiveness in vivo in patients with COPD and smokers with normal lung function. In 9 patients with COPD (mean (range) FEV, 55 (30-78) %predicted) and 8 smokers with normal lung function (FEV1 101 (89-117) %predicted), who underwent surgery for lung cancer, responses to inhaled histamine and salbutamol were assessed before surgery. Bronchial specimens of 1-4 mm internal diameter were studied in the organ bath and hista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In a study by Kanner et al, the prevalence of BHR in subjects with mild COPD varied between 25-48%; furthermore, the prevalence of BHR was reported to be approximately 66% in mild or early COPD subjects in the Lung Health Study [21,22]. However, a study by Taube et al of nine subjects with stable, mild to severe COPD found a positive challenge test for all nine subjects after administering inhaled histamine [23]. Asthma patients were excluded from our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kanner et al, the prevalence of BHR in subjects with mild COPD varied between 25-48%; furthermore, the prevalence of BHR was reported to be approximately 66% in mild or early COPD subjects in the Lung Health Study [21,22]. However, a study by Taube et al of nine subjects with stable, mild to severe COPD found a positive challenge test for all nine subjects after administering inhaled histamine [23]. Asthma patients were excluded from our study.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, while subsegmental bronchi provide the greatest airway resistance along the bronchial tree, the contribution of bronchioles to airway resistance is very limited (Brooks, 1995;Thien, 2013). Indeed, the ASM tone detectable in medium isolated bronchi is related to the change in forced expiratory volume in 1 s (FEV 1 ) (Brown et al, 2006;Rogliani et al, 2015;Rogliani, Ritondo, Facciolo, et al, 2021b;Taube et al, 2006). On the other hand, the luminal area of small isolated airways is related to the forced expiratory flow between 25% and 75% of vital capacity (FEF 25-75 ), that is a predictive marker of peripheral obstruction leading to small airway disease (SAD) in the so-called 'silent zone' (Hogg et al, 2013;Kwon et al, 2020;Martin et al, 2013;Rogliani et al, 2015Rogliani et al, , 2023Usmani et al, 2021) (Figure 3a,b).…”
Section: Human Medium Bronchi and Small Airwaysmentioning
confidence: 99%
“…This is supported by the observation that resected airway smooth muscle from patients with COPD with in vivo direct AHR does not demonstrate ex vivo AHR. 5 Direct AHR in patients with COPD is also significantly associated with gas trapping/hyperinflation. 6 Patients with COPD who also have asthma (some would call this ''COPD and asthma,'' and others would use the term ''asthma-COPD overlap syndrome'' or ACOS) will also manifest asthmatic AHR, including indirect AHR.…”
Section: Ahr and Copdmentioning
confidence: 99%